PARAGARD AND MIRENA AS MODERN INTRAUTERINE DEVICES - Theiva Amirta Sukantan; I N Toya; I G M Adioka (Bali Journal of Medical and Health Sciences, 2013)
There are two kinds of modern IUDs: Copper-bearing and progestin-releasing. IUD stands for IntraUterine Device, a T-shaped piece of plastic that is placed inside the uterus. The most common copper-bearing IUD is the Paragard[R] Copper T 380A. The only progestin- releasing IUD now available is Mirena[R]. The copper IUD, ParaGard, works for as long as 12 years. Copper based intrauterine devices are toxic to sperms and are also known as non- hormonal intrauterine devices. The hormonal IUD, Mirena, must be replaced after 5 years. This device functions by releasing levonorgestrel, a progestin that helps in contraception. This type of IUDs prevents the fertilization of the egg by causing sperms to become ineffective and also makes the mucus in the cervix sticky and almost impermeable. Both types make it more difficult for sperm to fertilize the egg.